TREATMENT OF EXTENSIVE PURULENT-NECROTIC LESIONS OF THE LEG IN PATIENTS WITH NEUROPATHIC FORM OF DIABETIC FOOT SYNDROME - Krivikhin, V. T.; Krivikhin, D. V.; Chernobay, A. V.; Lobakov, A. I.; Bakunov, M. Yu (Alʹmanakh klinicheskoĭ medit͡s︡iny, 2016)
Background: The development of purulent-necrotic complications in patients with diabetic foot syndrome (DFS) is a cause of high amputations, early disablement, resulting in development of metabolic syndrome and progression of cardiovascular complications. Today, the methods of treatment of purulent-necrotic lesions in DFS are aimed at preserving the supporting function of an extremity. The presence of extensive purulent-necrotic leg wounds is a risk factor of urgent indications for amputation. Aim: To develop an algorithm of treatment of extensive purulent-necrotic leg wounds in patients with neuropathic form of DFS. Materials and methods:  At the Regional Center “Diabetic foot” on the basis of Vidnoe regional clinical hospital, during a period of 2009 to 2013, the treatment results were analyzed in 62 patients with neuropathic form of DFS and extensive purulent-necrotic leg wounds. All patients underwent an active surgical intervention together with the complex conservative therapy. Treatment consisted of several stages: wound cleansing up to the appearance of granulation tissue – autodermoplasty – stimulation of epithelization. The efficiency of treatment was assessed depending on the time needed for wound cleansing, granulation, epithelization, and on the number of high amputations. Results: All patients underwent primary radical surgery to cross the pathways of purulent infection spreading in the proximal direction followed by an open management of the wound. Subsequently, the staged necrectomies were carried out along with a conservative therapy aimed at wound cleansing. The average time of wound cleansing was 10.6±1.2 days. Formation of granulation tissue took 8.4±0.8 days after the first surgery. When the purified granulation tissue was obtained, the patients underwent autodermoplasty with a free split tissue flap to stimulate epithelization. The process of epithelization started on the 10.2±0.6 day. At the admission to the hospital, on the 4-10th day after the first surgical intervention, an index of leukocyte infiltration was measured. Normalization of this index during treatment is indicative of the successful wound cleansing and satisfactory course of the wound healing. A single (1.6%) high amputation was performed in this group of patients within the period of 2009 to 2013. Conclusion: Active surgical tactics involving excision of the primary purulent focus, intersection of purulent pathways (tendons, fascia), open management of the wound, and subsequent staged necrectomies combined with a conservative therapy – all contribute to the maximum wound cleansing, reduction of intoxication level, and activation of reparative process. Timely autodermoplasty accelerates the process of epithelization and wound healing.